Eficacia de la prueba de amplificación genética por reacción en cadena de polimerasa y del cultivo de Mycobacterium tuberculosis, en muestras obtenidas por biopsia pleural con aguja, en pacientes con derrame pleural: Efficacy of the genetic amplification test by polymerase chain reaction and culture of Mycobacterium tuberculosis, in samples obtained by pleural needle biopsy, in patients with pleural effusion - Alquízar-Horna, Oscar Neri (2022)
Objetive: To compare the accuracy of the polymerase chain reaction (PCR) genetic expansion test and the culture for M. tuberculosis (BK culture) in parietal pleura samples obtained by pleural needle biopsy. Methods: 39 patients with lymphocytic or mononuclear exudative pleural effusion suspected of pleural tuberculosis were studied. A pleural biopsy with Abrams or Cope needle was performed on each of them and histopathological study, culture for M tuberculosis and PCR test were performed on the samples obtained. Additionally, other diagnostic tests and follow-up were performed to determine the response to treatment and establish the final diagnosis, based on previously established criteria. Results: Twenty-five patients met the criteria. Tuberculosis was diagnosed in twenty patients and four cancers. In one patient, chronic pleuritis associated with another process was diagnosed. For the PCR test the sensitivity was 85%, the specificity 20%, the predictive value of the positive test (PPV) was 81%, the predictive value of the negative test (NPV) of 25% and the efficacy was 72%. For the culture of M. tuberculosis, the sensitivity was 45%, the specificity, 100%; the PPV, 100%; the NPV was 31.25% and the accuracy was 56%. Conclusion: It is concluded that the PCR test is more accuracy than the BK culture, but with a low specificity, something unusual that would depend on the contamination of the sample.